Optimizing Reduced-Lead ECG Diagnosis: An Interpretable Pipeline for Lead Selection and Model Adaptation - Porfírio, Luisa G.; Evangelista, Guilherme H. G.; Rigueira, Pedro B.; Grossi, Caio Souza; Xavier, Artur; Mello, Victoria Andrade Flores de; Teodoro, Raquel; Dutenhefner, Pedro; Paixão, Gabriela M. M.; Pappa, Gisele L.; Ribeiro, Antonio; Meira Jr., Wagner (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e Computacional, 2025)
The 12-lead electrocardiogram (ECG) is vital for heart diagnosis but mostly limited to clinics due to its complexity. Wearable devices use fewer electrical viewpoints (leads), democratizing cardiac care by enabling monitoring at home or in low-resource settings. This shift raises two key challenges: selecting the most informative leads and adapting AI models to keep accuracy. We tackle this with a data-driven pipeline that ranks leads by combining multiple model-interpretability methods. Our evaluation shows that a model architecturally adapted to use only the top two leads (V1, I) achieves a macro F1-score of 0.885, matching the full 12-lead baseline. This work provides a framework for efficient, powerful AI systems, advancing accessible cardiac diagnostics.